Proyecto de factibilidad para la creación de un hotel en la ciudad de tarapoa del cantón Cuyabeno, provincia de Sucumbíos. - Aguilar Ponce, Grace Carolina (2014)
The project's overall objective Develop a "DRAFT FEASIBILITY FOR ESTABLISHING A HOTEL IN THE CITY TARAPOA OF THE CANTON CUYABENO, SUCUMBÍOS PROVINCE" To carry out the same research field where relevant data were performed to be analyzed to determine the supply and demand of hotel service in the city Tarapoa of the canton Cuyabeno. The methods used are deductive, inductive, statistical, descriptive method; between the techniques used are documentary and archival literature review, direct observation, survey and interview. After analyzing the results, we conclude that: In the Market Study has identified a potential demand of 83,698 tourists identify Tarapoa city as a place for tourism, real demand of 83,698 people visited the city in Tarapoa Canton Cuyabeno, effective demand of 83,004 tourists would use the hosting service in the new hotel, an average annual use of 6 per tourist lodges a year, resulting in an effective annual demand of 484,897 per person Accommodation in a year. Furthermore it was established that the offer of accommodation services market is 21,600 tourists a year, giving an unmet demand for 463,297 tourist’s lodges in the base year. The Technical Study conducted get that installed capacity is of 16,560 guests a year, while 13,248 Guest capacity utilization in the first year using 80% of the installed capacity. Also the size and location of the project is presented, this hotel company is located in the Cuyabeno Canton Sucumbios Province, attaching the plane of the physical layout of the plant, the engineering project is the production process at all stages. Regarding Organizational and Management Study, the legal organization established as a limited liability company that will have three members, whose corporate name is proposed "HOTEL CUYABENO CIA LTDA."; administrative organization arises through charts and manual functions. The Financial Studio is stated that the creation of the company investing $ $ 78,509.89 is required. The founding partners contribute $ 28,509.89, the, 36% of investment and 64% with a credit for the amount of $ 50,000.00. The Income Statement shows a net income of $ 20,643.07 in the first period, the cash flow is $ 29,839.54 in the first year. The evaluation of the project showed that the net present value is positive with a value of $ 13,668.80; the internal rate of return is 24.69% is greater than the opportunity cost of capital of 12%, the cost-benefit ratio indicates that for every dollar spent 45 cents of performance will be obtained, the investment will pay off in two years, nine months and 27 days; and, based on the sensitivity analysis demonstrates a satisfactory result allowing 11.01% increase in costs and a decrease in revenue of 9.06%. Demonstrating that the project is feasible and profitable for the investor which execution is recommended due to its high yield and its important contribution to the entrepreneurial city in the canton Tarapoa Cubayeno and Sucumbios.